Rings and gaps in the disc around Elias 24 revealed by ALMA. Issue 4 (23rd January 2018) - Dipierro, G; Ricci, L; Pérez, L; Lodato, G; Alexander, R D; Laibe, G; Andrews, S; Carpenter, J M; Chandler, C J; Greaves, J A; Hall, C; Henning, T; et al.
Abstract: We present Atacama Large Millimeter/sub-millimeter Array (ALMA) Cycle 2 observations of the 1.3-mm dust continuum emission of the protoplanetary disc surrounding the T Tauri star Elias 24 with an angular resolution of ∼0.2 arcsec (∼28 au). The dust continuum emission map reveals a dark ring at a radial distance of 0.47 arcsec (∼65 au) from the central star, surrounded by a bright ring at 0.58 arcsec (∼81 au). In the outer disc, the radial intensity profile shows two inflection points at 0.71 and 0.87 arcsec (∼99 and 121 au, respectively). We perform global three-dimensional smoothed particle hydrodynamic gas/dust simulations of discs hosting a migrating and accreting planet. Combining the dust density maps of small and large grains with three-dimensional radiative transfer calculations, we produce synthetic ALMA observations of a variety of disc models in order to reproduce the gap- and ring-like features observed in Elias 24. We find that the dust emission across the disc is consistent with the presence of an embedded planet with a mass of ∼0.7  M J at an orbital radius of ∼ 60 au. Our model suggests that the two inflection points in the radial intensity profile are due to the inward radial motion of large dust grains from the outer disc. The surface brightness map of our disc model provides a reasonable match to the gap- and ring-like structures observed in Elias 24, with an average discrepancy of ∼5 per cent of the observed fluxes around the gap region.